Comportamento microclimático urbano: estudo de caso de um recorte urbano em João Pessoa-PB - Duarte, Manuela de Luna Freire (2010)
Rapid urbanization generates impacts on climatic variables favoring the occurrence of problems such as heat islands and temperature inversions. The knowledge of the climatic characteristics of the urban environment is one way to reverse or mitigate the effects caused by urbanization. The work aims at investigating the behavior of an urban microclimate area surrounding the Silvio Porto Square in João Pessoa - PB. It also tries to correlate the behavior of temperature, humidity and wind speed with vegetation and morphological characteristics of the urban environment. These variables were monitored by using a fixed station and a mobile measuring system for eight consecutive days in the morning, afternoon and at night. The results indicated that morphological variables as sky-view factor, the hours of solar radiation and wind speed have greater influence on temperature increase than the proximity to the existing vegetation in the Silvio Porto Square.